Chronic Pulmonary Embolism and Pulmonary Hypertension - Klok, Frederikus A.; Mos, Inge C.M.; van Kralingen, Klaus W.; Vahl, Jelmer E.; Huisman, Menno V. (Seminars in Respiratory and Critical Care Medicine, 2012)
Incomplete resolution of acute pulmonary embolism (PE) is frequently observed after acute PE and may rarely result in chronic thromboembolic pulmonary hypertension (CTEPH). The underlying pathophysiological mechanism is largely unknown. Evidence underlines the concept of a dual pulmonary vascular compartment model consisting of increased pulmonary vascular resistance by both large vessel obstruction and distal small vessel obliteration, the latter initiated by pathological vascular remodeling. Up to 40% of patients with established CTEPH have no prior history of symptomatic venous thromboembolism. CTEPH is associated with a poor prognosis if left untreated. Therefore, the diagnostic approach of CTEPH aims at assessing the location and extent of the embolic obstruction, establishing the operability and prognosis of the patients and ruling out other variations of pulmonary hypertension with distinct indicated treatment. Heart catheterization for invasive pressure measurements and pulmonary catheter angiography is obligatory for the final diagnosis. Pulmonary thromboendarterectomy is the treatment of choice. In certain patients with persistent or recurrent pulmonary hypertension after surgery or with inoperable disease, pharmacotherapy might be beneficial.
Keywords: pulmonary embolism; chronic thromboembolic pulmonary hypertension; diagnosis; therapy; prognosis